Enhanced transient expression of an anti-CD52 monoclonal antibody in CHO cells through utilization of miRNA sponge technology - Morvarid Sadat Pairawan; Azam Bolhassani; Azam Rahimpour (Wolters Kluwer Medknow Publications, 2019)
Chinese hamster ovary (CHO) cells are the dominant mammalian host system for the production of recombinant therapeutic proteins. Improving the viable cell density during culture of recombinant CHO cells can greatly affect the production yield. MicroRNAs (miRs) -15a and 16-1 are known as negative regulators of multiple genes involved in cell cycle progression and apoptotic inhibition. miR sponges, which act as decoy targets, are transcripts which contain complementary binding sites to the seed region of related miRs. Stably expressed miR sponges are known as efficient tools for miR loss of function studies. In this study, stable CHO cell pools and clones expressing miRs-15a and 16-1 specific decoy transcript downstream of an enhanced green fluorescent protein reporter gene was developed. Analysis of cell growth during 12 days of batch culture indicated improved maximum viable cell density of CHO cells and clones expressing the decoy transcript. In addition, transient expression of a recombinant anti-CD52 monoclonal antibody was significantly improved in a decoy harboring CHO cell clone, representing a 3.37-fold increase in yield after 4 days of culture. Our results indicated that miR sponge technology can be successfully applied for the improvement of cell viability and transient monoclonal antibody expression in CHO host cells.